AKTIVITAS KELENJAR TIROID TIKUS PUTIH (Rattus norvegicus Berkenhout, 1769) JANTAN PADA INDUKSI HIPOTIROID - , MUSTIKA SARI, Dra. Mulyati, M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Thyroid hormone is essential for growth, development, and homeostasis of vertebrate organisms. Abnormal activity of the thyroid gland can affected growth and development. Hypothyroidism is a disorder in the of low activity of thyroid gland. The purpose of this study is to know activity of the thyroid gland in the male rats induced by Propiltiourasil. Research design using Factorial Complete Randomized Design (FCRD) with 2 factors. Wistar rats hypothyroidism was induced by oral administration 0,05% propiltiourasil (PTU) for 21 days in two route by ad libitum and oral gavage for 4 age groups of 4, 5, 6, and 7 weeks. Activity of the thyroid gland was analyzed by measurement of level T3 and T4 hormones using Immunosorbant Enzyme Linked Assay (ELISA) and Ephitelial Folicel Index (EFI) the thyroid gland. The results showed induction of hypothyroidism by PTU decrease the activity of thyroid gland rats at all ages. The highest activity decrease occurred at the age of 4 weeks. Induction of hypothyroidism by oral gavage was significantly decreased levels of the T4, T3 hormone and EFI while induction by ad libitum decreased T4 hormone levels and no significantly on the T3 levels and thyroid gland EFI. In hystopatology the thyroid gland of rats revealed hypertropy epithelial and hyperplasia ephitelial cells, decreased folicel dyameter and colloid mass.